RI 5641 Laboratory Treatment Of California And Nevada Manganese Ores By Sulfation-Reduction And Other Methods ? Introduction And Summary - A. L. Engel (The National Institute for Occupational Safety and Health (NIOSH), 1960)
This publication describes further research by the Federal Bureau of Mines in beneficiating domestic manganese ores. The ores selected for treatment were typical of many manganese deposits in California and Nevada in that they have not been economical to mine because they are low grade or contaminated with siliceous minerals and are not amenable to physical concentration.3 4/ It would be desirable to develop a simple treatment method resulting in nearly complete extraction of manganese from these ores and applicable to small-scale operations. Sulfation reduction appeared to be such a method. The studies reported in this publication were directed toward sawdust or lignin-sulfonates as reducing agents. Sawdust, as waste from lumbering, and lignin-sulfonates, byproducts of woodpulp papermaking, are comparatively cheap and may be available in areas where manganese ores are found. Sugar, oils, and coal were also tried as reducing agents.